Organizational Factors that Affected Training Participation among Academic Staff based on Training Officers’ Perception: a Qualitative Research at a Malaysian Public University - Syah Mokhtar, Ikram; Hazana Abdullah, Nor; Mahmood Salman, Peshraw; Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
Training and development are seen as an important tool for organizational needs. Many organizations are now more likely to emphasizn the aspects of training and development as a way to promote the development of workers to achieve ahighly skilledd workforce. Staff participation in trainingprogramss is essential toimprovinge the ability of employees and the trust to carry out the assigned tasks.Referringr to these requirements, this study aims to continuously explore organizational factors affecting the participation of academic staff at public universities in Malaysia inprograme training. This study has been using a qualitative method whereby a total of seven (7) officers from a university in Malaysia were interviewed. The data obtained was analysed usingthe Nvivo100 application. Based on the analysis) eight identified organizational factors are training policies, preventive measures, talent management, management commitments, university training culture, financial constraints, trainingfacilities,s and facilities management. It is hoped that the findings of this study can be utilized by any interested parties, especially for the Training Division of the Malaysian public universities as well as the Ministry of Higher Education Malaysia (KPTM).